Physio-morphological and biochemical mechanism of nitrogen use efficiency in sugarcane (Saccharum spp.) genotypes under different growth stages and nitrogen levels. Issue 1 (1st January 2021) - Anas, Muhammad; Verma, Krishan K.; Riaz, Muhammad; Qiang, Li; Liao, Fen; Liu, Yang; Li, Yang-Rui
ABSTRACT: Nitrogen is crucial for sugarcane crop to get economical sugar and biofuel throughout the world, and low nitrogen use efficiency is the main issue of sugarcane because of high nitrogen losses. In this experiment, physio-morphological, growth, and biochemical traits were observed for sugarcane genotypes (nitrogen inefficient-GT11 and efficient GXASF180-1-11) under 0.05 and 5 mMN levels at 5, 7, and 9 leaf stages. GXASF180-1-11 attained 46–58% and 16–23% more plant height and biomass than GT11, while photosynthesis and internal nitrogen use efficiency (iNUE) were 16 and 8% more at F2 fertilizer level, respectively. Highest key enzymes activity was showed in leaf whereas polynomial regression ranged between 0.53 and 0.98, 0.69 and 0.99 for iNUE and nitrogen use index. Principal component analysis explained 91.23–93.53% total variance across the stages. These results suggested that low nitrogen application rate with efficient germplasm may have the potential to improve iNUE for further cultivar development.